Utilization of Information Technology in Women Boarding High Schools to Support Learning Activities - Wildan Suharso; Moch Imron; Ekanita Rakhmah; Lathifah Hanif; Didih Rizki Chandranegara (Universitas Muhammadiyah Malang, 2020)
The use of information technology media becomes very important when the needs are increasingly complex or schools are in the development stage because with the use of information technology media teaching and learning activities can be carried out quickly and centrally. In female boarding schools, the use of technology really needs to be considered considering the activities that are so dense both intraculricular and extracurricular activities, on the other hand, Aisyiyah Boarding School Malang High School has quite high activities outside the school, this is evidenced by the many achievements they have from the local to the national level. . At the time this research was conducted, all countries in the world were experiencing the Covid-19 pandemic and required all activities to run online, so this research was conducted to determine the use of information technology at ABSM High School to support teaching and learning activities. The variables used in the study include new desire and interest in learning, motivation and interest in learning, understanding in learning. The research method includes research assumptions and definitions, data collection, analysis of initial conditions, preparation of questionnaires, descriptive analysis. Respondents were students of class X, XI, and XII of SMA ABSM, with a total of 30 respondents who were all ABSM high school students. The results show that in general the use of information technology media can support the teaching and learning process in the school environment for both intraculricular and extracurricular activities.